Tantangan Profesional Guru di Era Digital: Tinjauan Literatur Sistematis - Aditya Cahyo Pratama; Ruhaina Juwita Sari; Farihah; Halimul Bahri (Fakultas Tarbiyah Institut Pesantren Sunan Drajat Lamongan, 2026)
The rapid development of digital technology has brought significant changes to the world of education, particularly to the roles and responsibilities of teachers. This study aims to analyze the various challenges teachers face in carrying out their profession in the digital era. The method used is a qualitative approach with a literature review of various relevant scientific sources. The results indicate that teachers face several key challenges, including limited digital competency, a lack of ongoing training, disparities in technology access, and changing student characteristics that are increasingly adapting to technology. Furthermore, the demand to effectively integrate technology into the learning process also poses a challenge. Therefore, efforts are needed to improve teacher competency infrastructure through digital training, educational policy support, and the provision of adequate resources. In conclusion, teachers are required to continuously adapt and develop themselves to optimally fulfill their role in facing the dynamics of education in the digital era.